2017
DOI: 10.1038/s41467-017-01442-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal percolation on multiplex networks

Abstract: Optimal percolation is the problem of finding the minimal set of nodes whose removal from a network fragments the system into non-extensive disconnected clusters. The solution to this problem is important for strategies of immunization in disease spreading, and influence maximization in opinion dynamics. Optimal percolation has received considerable attention in the context of isolated networks. However, its generalization to multiplex networks has not yet been considered. Here we show that approximating the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 53 publications
1
65
0
Order By: Relevance
“…Is it possible to safeguard some nodes so that the sufficient condition that the network will be in the functional state is met? Please note that the latter question is different from the one defined in optimal percolation, where the goal is to dismantle a system rather than preserving its cohesiveness [33,37].…”
Section: Safeguarding the Mcgcmentioning
confidence: 99%
See 2 more Smart Citations
“…Is it possible to safeguard some nodes so that the sufficient condition that the network will be in the functional state is met? Please note that the latter question is different from the one defined in optimal percolation, where the goal is to dismantle a system rather than preserving its cohesiveness [33,37].…”
Section: Safeguarding the Mcgcmentioning
confidence: 99%
“…In order to investigate whether the top-ranked nodes according to ∆s have some relation with the nodes identified in solutions to the optimal percolation problem, we performed systematic comparisons between the top 5 nodes according to ∆s and various methods used in optimal percolation [37]. We find that the top-ranked nodes correspond with good accuracy to the nodes in the optimal structural set detected by Simulated Annealing optimization [37]. High correlation (measured using Kendall τ ) is also found with sets determined using other state-ofthe-art techniques (see Table II).…”
Section: Safeguarding the Mcgcmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that an effective way to destroy the giant component of a single network, i.e., destruction of the 2-core, does not carry over to multilayer networks. The methods of effective multiplex degree [56] and optimal percolation [57] were articulated for multilayer networks to find the minimal damage set that destroys the largest mutually connected component.…”
Section: Introductionmentioning
confidence: 99%
“…In [10] belief propagation is used to find efficient shattering sets. In [11] optimal attacks on multiplex networks are studied using simulated annealing methods.…”
Section: Introductionmentioning
confidence: 99%